2003
DOI: 10.3171/foc.2003.15.4.0
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous intracerebral hemorrhage: a review

Abstract: Spontaneous intracerebral hemorrhage (SICH) is a blood clot that arises in the brain parenchyma in the absence of trauma or surgery. This entity accounts for 10 to 15% of all strokes and is associated with a higher mortality rate than either ischemic stroke or subarachnoid hemorrhage. Common causes include hypertension, amyloid angiopathy, coagulopathy, vascular anomalies, tumors, and various drugs. Hypertension, however, remains the single greatest modifiable risk factor for SICH. Computerized tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
2
34

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(128 citation statements)
references
References 129 publications
(149 reference statements)
2
90
2
34
Order By: Relevance
“…We propose that histogram analysis is a useful tool for detecting hidden solid tumor lesions within acute ICH, which might be helpful in establishing appropriate imaging follow-up and avoiding delays in long-term management of tumorous ICHs. Vascular malformation, another common cause of secondary ICH, 6,7 showed relatively higher attenuation, similar to that of primary ICH, and thus could be discriminated from tumorous ICH. One explanation for this result is that rupture of abnormal vessels is the main pathophysiology of acute bleeding.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We propose that histogram analysis is a useful tool for detecting hidden solid tumor lesions within acute ICH, which might be helpful in establishing appropriate imaging follow-up and avoiding delays in long-term management of tumorous ICHs. Vascular malformation, another common cause of secondary ICH, 6,7 showed relatively higher attenuation, similar to that of primary ICH, and thus could be discriminated from tumorous ICH. One explanation for this result is that rupture of abnormal vessels is the main pathophysiology of acute bleeding.…”
Section: Discussionmentioning
confidence: 97%
“…1 Tumors account for 10% of all spontaneous ICH cases. 6,7 Earlier discrimination of tumorous etiology from nontumorous causes of acute ICH might be helpful to determine appropriate imaging follow-up and avoid delays in long-term management of tumorous ICH, though acute management would not differ. Nonenhanced CT (NECT) is the standard investigation tool for acute ICH.…”
mentioning
confidence: 99%
“…Criterias on treatment decision include; patient's age, hematoma volume, location and deepness from the surface, Glasgow coma scale (GCS), pathologies underlying hematoma (aneurysm, AVM, trauma etc. ), time duration between hemorrhage and diagnosis, severe coagulopathy or presence of underlying serious medical disease, progression on neurological deficits or conscious, development of obstructive hydrocephaly, and compression of brain stem (3,8,9). However, The STICH (surgical treatment for intracerebral haemorrhage) study showed no overall benefit from early surgery when compared with initial conservative treatment (25).…”
Section: Discussionmentioning
confidence: 99%
“…If there is an underlying pathology of the hematoma, intervention should also be performed to that lesion during the surgery (3,8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation